Environmental degradation of electroplated nickel and copper coated SS316H in molten FLiNaK salt. (October 2021) - Weinstein, Matthew; Falconer, Cody; Doniger, William; Bailly-Salins, Louis; David, Raphaelle; Sridharan, Kumar; Couet, Adrien
Highlights: Nickel and copper electroplated coatings resist corrosion in molten FLiNaK. Nickel and copper coatings prevent corrosion of substrate material in FLiNaK. Copper coatings and SS316H exhibit little interdiffusion at 700 C in molten FLiNaK. Nickel coatings reduce substrate mass loss in FLiNaK despite interdiffusion. Abstract: Corrosion of nickel and copper electroplated coatings on SS316H in molten FLiNaK salt was studied. 500- and 1000-hour static corrosion tests were performed in molten FLiNaK at 700 degrees Celsius. Characterization of the coatings following corrosion indicated that they did not degrade in the molten salt during the corrosion experiment and fully protected the underlying SS316H from chromium dissolution. Interdiffusion between the copper coating and SS316H was extremely limited, interdiffusion between the nickel coating and SS316H. Diffusion modelling revealed that the nickel coatings still significantly reduced chromium dissolution over 60 years despite the interdiffusion.